(1488) A multi objective optimization model for the new cities and settlements of Sinai نموذج تحسين متعدد الأهداف للمدن والمستوطنات الجديدة في سيناء - Omar, Amani (The Institute of National Planning, 2018)
Selecting tracts of land fo development settlements, reaction of towns, industrial parks, air field or many other uses may be considered as a land allocation problem.